Doa di Zaman Digital - Wicaksono, Agung (Lux et Sal, 2024)
It is undeniable that the implementation of information technology in the digital era has permeated various fields and aspects of life, including its contribution to an individual's spiritual existence. Despite the myriad of positive and negative impacts it generates, technology fundamentally possesses a neutral nature. The Catholic Church, as an institution that shepherds the faith of billions of Catholics worldwide and serves as a moral compass for humanity, also addresses the repercussions brought about by the changes and advancements in technology within this digital age. This paper seeks to explore the essential aspects that need to be championed, the boundaries that must be acknowledged, and the potentials that can be developed to ensure that the application of information technology in the digital era maximizes the development of one's spiritual life.